Superação de desordem fisiológica e qualidade de frutos de abacaxi turiaçu, em função de boro e biofertilizante foliar - Sousa, Eduardo Henrique Santana (2015)
This research aims to evaluate the reduction of symptoms of cork injury and general improvement in the quality of Turiaçu pineapple fruit, depending on foliar application of B in mineral form and via bio-fertilizer. The work was conducted in the municipality of Turiaçu-MA. The treatments consisted of foliar application of B mineral and biofertilizer at a concentration of 0.3%, according to the scheme: control (no B); B applied four months after planting; applied eight months; applied 12 months; applied at 4, 8:12 and biofertilizer applied at 4, 8 and 12 months. The design was a randomized blocks, with 4 replicates and 6 treatments on the application of B. The data were submitted to ANOVA, the F test and means were compared by testing the average level of 5%. Analysis of correlations have been established to seek to explain cause and effect. Plants and fruits were evaluated on their chemical and nutrition, growth, number of lesions. The application of boric acid to boron via the 4, 8 and 12 months reduced the number of lesions corticosas surface. The application of boric acid to boron via the 4, 8 and 12 months reduced the number of lesions corticosas surface. The application of boric acid to boron via the 4, 8 and 12 mon ths gave the highest levels of boron in both chlorophyllated as part of the sheet in aclorofilada D. Application of boron, boric acid via biofertilizer and route, and the doses and experimental conditions , did not reduce the number of typical corticosas injuries. The application of boron, boric acid and route via biofertilizer, and the doses and experimental conditions, did not affect the chemical and physical characteristics of fruits, vegetative and reproductive plant except the length / width ratio foil D.